PROSES PEMBELAJARAN TATAP MUKA DI TENGAH WABAH COVID-19 DI MTS AL-IMAN WAY JEPARA: Muhamad Juana dan Laila Nursafitri - Muhamad Juana; Laila Nursafitri (LPPM STAI Darussalam Lampung, 2022)
Abstract This study aims to examine the face-to-face learning process at MTs Al-Iman Way Jepara during the Covid-19 pandemic. The data from this study were obtained from observation, interviews, and documentation. The results of this study indicate that the face-to-face learning process has a positive impact on students, such as students receiving direct guidance from the teacher, students can socialize well among friends, and students can take advantage of school facilities. Meanwhile, the face-to-face learning process applied at MTs Al-Iman during this pandemic is generally still the same as that applied on normal days, it's just that the difference is that the time allocation is simplified / accelerated. This is considering the Health protocol that has been implemented by the government. The contribution of this research to education in Indonesia is to provide an overview of the National Education Institution of the importance of face-to-face learning. Given that it has been one year students have not enjoyed the learning process in the classroom